(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To find out the incidence and etiology of ventilator-associated pneumonia in pediatric intensive care units. Subjects and research methods: Descriptive study of 296 patients requiring mechanical ventilator ≥ 48 hours at Nghe An Obstetrics and Pediatrics Hospital from June 2022 to May 2023. Results: 83 patients suffered ventilator-associated pneumonia with 98 episodes that met the criteria for ventilator-associated pneumonia. The incidence rate reached up to 28% and 22.5/1000 mechanical ventilator days. The most frequently isolated mico-organisms were Acinetobacter baumannii (23.6%), followed by Klebsiella pneumoniae (19.4%) and Pseudomonas aeruginosa (12.5%). Compared with non-ventilator-associated pneumonia group, ventilator-associated pneumonia were closely related to more prolonged ventilator, intensive care unit stay time and hospitalization time. Conclusion: The incidence of ventilator-associated pneumonia in this study was relatively high, and strict supervision of infection control protocols was crucial.